Evaluasi Penggunaan Software Lathe Simulator Dengan Menggunakan User Experience Questionaire - Prasetyo, Rian; Sari, Maria Puspita; Suprapto, Suprapto; Sari, Marta Hayu Raras Sita Rukmika (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2022)
Manufacturing industry is one of industrial sector in Indonesia that interesting to research. Based on Indonesian GDP in 2015, this sector has a contribution up to 21.13 percent. Most of production process in manufacturing industry used to machining process. One of them is lathe. Moreover, HR preparation is needed, due to have knowledge about this machine. One of them is using machine simulator called “Lathe Simulator 1k62”. The purpose of this research is to find out user experienced of “Lathe Simulator 1k62”. The research method is giving several tasked to respondent, then to fill the User Experienced Questionnaire (UEQ) to find out the Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. The result found that all of the respondent had complete the assigned task. The UEQ, found that “Lathe Simulator 1k62” in generally had positive value, based on Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty all above 0.8. Furthermore, user experienced of “Lathe Simulator 1k62” had “good” category compared to other software.Keywords: User Experienced, UEQ, Usability, Simulator